(untitled) (The International Research Journal of Management Science, 2025)
Purpose – Purpose: This study aims to explore the critical challenges in embedding sustainability in Nepalese HEIs and provides measures to address them. Design/methodology/approach: Grounded in an interpretivist philosophy, this qualitative study employs an exploratory research design. Data were collected through semi-structured interviews with 15 HEI officials (including academics, deans, planning chiefs, and vice-chancellors) from two major Nepalese universities. A purposive sampling technique was used to ensure diverse perspectives. The data were analyzed to identify, rank, and thematically categorize the primary challenges. Findings: The analysis reveals that the most severe challenges are structural and systemic. The top-ranked barriers include traditional organizational structures, disciplinary barriers, and insufficient institutional capacity; insufficient financial resources and a lack of administrative support; unscientific reward systems that do not incentivize sustainability efforts; and the ineffective integration of sustainability into teaching and operations. These are compounded by cultural, governance, and external relational challenges. Addressing these challenges and embedding sustainability in HEIs, they need to adopt a phased, systemic approach: establish sustainability offices, revise incentives, and enhance ICT (within 1 year); integrate SDGs into curricula, green campus operations, and modernize governance (1–2 years); and foster equity-focused policies, industry partnerships, and context-specific evaluation tools (2 + years) to embed sustainability institutionally and culturally. Research limitations/implications: The study’s main limitation is its exclusive focus on leadership perspectives, offering only a top-down view and omitting broader stakeholder experiences within the HEIs. Practical implications: To overcome key challenges, Nepalese HEIs must adopt a holistic, "whole-institution" approach. Practical measures include revising governance models to establish sustainability-focused units, overhauling reward systems to recognize sustainability contributions, investing in capacity development for staff, integrating sustainability across curricula, and fostering stronger industry-academia partnerships. Originality/value: This study provides a context-specific, prioritized ranking of the challenges to implementing sustainability in the under-researched setting of Nepalese HEIs. It moves beyond listing challenges to offering a structured framework for action, categorizing challenges into structural, cultural, relational, and knowledge-based themes to guide strategic intervention and resource allocation.